2003
DOI: 10.1007/s00244-003-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Residues in Livers of Bald Eagles ( Haliaeetus leucocephalus ) Found Dead or Dying in British Columbia, Canada (1987?1994)

Abstract: Postmortem examinations were conducted on 82 bald eagles (Haliaeetus leucocephalus) found dead or dying in British Columbia, Canada, from 1987 to 1994. As part of the examination, livers were analyzed for total mercury (Hg) content, as well as methylmercury (meHg) and selenium (Se) in selected individuals. In total, 67 eagles were classed as having low Hg exposure [total Hg liver residues ranging from 0.5 to 17.2 mg/kg dry weight (dw)]. Fourteen eagles were moderately exposed (liver residues ranging from 19.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Concentrations of Hg and/or Se in livers of common loons and bald eagles analyzed in the current study were comparable to ranges reported previously for these species (Wood et al 1996;Pokras et al 1998;Scheuhammer et al 1998;Bischoff et al 2002;Stout and Trust 2002;Weech et al 2004b). However concentrations of Hg and Se in brain tissue of these species have not been previously reported.…”
Section: Discussionsupporting
confidence: 84%
“…Concentrations of Hg and/or Se in livers of common loons and bald eagles analyzed in the current study were comparable to ranges reported previously for these species (Wood et al 1996;Pokras et al 1998;Scheuhammer et al 1998;Bischoff et al 2002;Stout and Trust 2002;Weech et al 2004b). However concentrations of Hg and Se in brain tissue of these species have not been previously reported.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, concentrations of THg in the liver averaged 7.97 lg/g and ranged from 0.47 to 61.61 lg/g. Bald eagles in British Columbia, Canada from 1987 to 1994 had a mean liver concentration of 11.8 lg/g and most birds fell in a range from 0.5 to 17.2 lg/g (Weech et al 2003). Liver concentrations in adult bald eagles collected in Florida from 1987 to 1993 ranged from 2.17 to 42.07 lg/g (converted from dry weight; Wood et al 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies on bald eagles across North America have documented appreciable Hg levels in eggs (Weimeyer et al 1993), feathers (Bowerman et al 1994;Wood et al 1996;Weech et al 2006;Bechard et al 2007), blood (Wood et al 1996;Weech et al 2006), liver (Wood et al 1996;Weech et al 2003;Scheuhammer et al 2008), and brain (Scheuhammer et al 2008). Though Hg exposure in bald eagles is fairly well understood, much less is known about adverse health effects that may be associated with such exposures.…”
Section: Introductionmentioning
confidence: 96%
“…Individual observations also show that beyond a certain concentration of MeHg in liver, the detoxification system of the body is disturbed and ceases to function efficiently. Then, sublethal and lethal poisonings occur, in which a very high concentration of hepatic THg is accompanied by a high %MeHg (>75%), as was the case in field studies on the bald eagle . However, the final confirmation of this suggestion requires much more data on the concentration of both THg and MeHg in the liver and other tissues of piscivorous species in field and laboratory studies.…”
Section: Discussionmentioning
confidence: 95%
“…More often, spatial and temporal differences in hepatic and nephric Hg and Se concentrations were observed among wintering and migrating bird groups of the same species [22][23][24]. Moreover, both hepatic and nephric Hg and Se concentrations have been different much more often when the examined individuals represent different condition groups [5,11,14,25,26].…”
Section: Comparisons Of Age and Condition Groupsmentioning
confidence: 99%